Boundary Crossings Resulting in Active Learning in Preservice Teacher Education: A CHAT Analysis Revealing the Tensions and Springboards Between Partners - Laferrière, Thérèse (Frontiers in ICT, 2018)
We present the results of a twenty-year long university-school partnership in which pre-service teachers collaborated with cooperative teachers and peers during their field experiences (practicums). The partnership evolved as a design experiment. Papers presented at AERA but never submitted to a research journal were revisited applying cultural-historical activity theory to understand the university-school partnership’s activity in terms of motive/object, instruments, community, roles, and rules/policies. We point to tensions that manifested contradictions between activity systems. Suggestions for boundary crossing when field experiences are part of an undergraduate program are made.